Duration of the first steps of the human rRNA processing - Popov, Alexey; Smirnov, Evgeny; Kováčik, Lubomír; Raška, Otakar; Hagen, Guy; Stixová, Lenka; Raška, Ivan (Nucleus, 2013)
Processing of rRNA in mammalian cells includes a series of cleavages of the primary 47S transcript and results in producing three rRNAs: 18S, 28S and 5.8S. The sequence of the main processing events in human cells has been established, but little is yet known about the dynamics of this process, especially the dynamics of its early stages. In the present study, we used real-time PCR to measure levels of pre-rRNA after inhibition of transcription with actinomycin D. Thus we could estimate the half-life time of rRNA transcripts in two human-derived cell lines, HeLa and LEP (human embryonic fibroblasts), as well as in mouse NIH 3T3 cells. The primary transcripts seemed to be more stable in the human than in the murine cells. Remarkably, the graphs in all cases showed more or less pronounced lag phase, which may reflect preparatory events preceding the first cleavage of the pre-rRNA. Additionally, we followed the dynamics of the decay of the 5'ETS fragment which is degraded only after the formation of 41S rRNA. According to our estimates, the corresponding three (or four) steps of the processing in human cells take five to eight minutes.
Keywords: NIH 3T3 Cells; RNA Processing, Post-Transcriptional; Transcription, Genetic; posttranskripční úpravy RNA; RNA, Ribosomal; prekurzory RNA; daktinomycin; HeLa buňky; genetická transkripce; Dactinomycin; RNA Precursors; Animals; lidé; HeLa Cells; RNA ribozomální; Humans; zvířata; myši; Mice; buňky NIH 3T3